Reduction of osteoclast formation and survival following suppression of cytokines by diacerein in periodontitis - de Oliveira, Gabriella [UNESP]; de Andrade Rodrigues, Lucas [UNESP]; Souza da Silva, André Acácio; Gouvea, Lays Cristina [UNESP]; Silva, Renata Cristina Lima [UNESP]; Sasso-Cerri, Estela [UNESP]; Cerri, Paulo Sérgio [UNESP] (Elsevier, 2024)
Periodontitis causes an increase in several bioactive agents such as interleukins (IL), tumor necrosis factor (TNF)-α and receptor activator of NF-kB ligand (RANKL), which induce the osteoclast formation and activity. Since diacerein exerts anti-TNF-α and anti-IL-1 effects, alleviating bone destruction in osteoarthritis, we investigated whether this drug inhibits the formation and survival of osteoclast in the periodontitis. Rats were distributed into 3 groups: 1) group with periodontitis treated with 100 mg/kg diacerein (PDG), 2) group with periodontitis treated with saline (PSG) and group control (CG) without any treatment. After 7, 15 and 30 days, the maxillae were collected for light and transmission electron microscopy analyses. Gingiva samples were collected to evaluate the mRNA levels for Tnf, Il1b, Tnfsf11 and Tnfrsf11b by RT-qPCR. In PDG, the expression of Tnf and Il1b genes reduced significantly compared to PSG, except for Tnf expression at 7 days. The number of osteoclasts reduced significantly in the PDG in comparison with PSG at 7 and 15 days. In all periods, the IL-6 immunoexpression, RANKL/OPG immunoexpression and mRNA levels of Tnfsf11/Tnfrsf11b ratio were significantly lower in PDG than in PSG. PDG exhibited significantly higher frequency of TUNEL-positive osteoclasts than in PSG and CG at all time points. Osteoclasts with caspase-3-immunolabelled cytoplasm and nuclei with masses of condensed chromatin were observed in PDG, confirming osteoclast apoptosis. Diacerein inhibits osteoclastogenesis by decreasing Tnf and Il1b mRNA levels, resulting in decreased RANKL/OPG ratio, and induces apoptosis in osteoclasts of alveolar process of rat molars with periodontitis.
Keywords: Alveolar bone loss; Apoptosis; Bone remodelling; Cytokines; Drug therapy; Osteoclasts; Periodontitis; RT-PCR